Opazovanje dejanja kot kognitivno sredstvo za rehabilitacijo po mišično-skeletnih poškodbah - Paravlić, Armin (Šport (Ljubljana), 2022)
Operative procedures, such as total knee arthroplasty and anterior cruciate ligament reconstruction surgery often lead to knee extensor muscle weakness, which can persist even years after the surgery. Despite the general techological development, less invasive surgical procedures and extensive postoperative rehabilitation, more than half of the patients do not return to preinjury levels of sports participation. Current rehabilitation practice after major knee operative procedures involves traditional approach to exercise, which mechanically stresses the musculoskeletal system. Such programmes include exercises for improving range of motion, gait re-education, weight-bearing exercise, training of the neuromuscular function and proprioception, as well as strength and endurance exercises, both performed voluntarily and by using electrical stimulation devices. Nevertheless, it seems that such programs are not sufficient in eliminating functional limitations after aforementioned surgical procedures. Therefore, it is necessary to explore new therapeutic tools that target the central nervous system or higher centers of motor control and include them in the existing rehabilitation practice. A variety of techniques for physical and mental activation have been developed for improving the physical funtion, when the movement execution is not possible (eg due to pain, impaired motor control and/or immobilisation). Among the most popular such cognitive techniques are motor imagery and action observation. This review decribes different cognitive strategies, which can potentially be implemented in the rehabilitation practice of the ortopedic patients.
Keywords: kognitivna vadba; koleno; mišičnoskeletni sistem; rehabilitacija; šport; športne poškodbe